1999
DOI: 10.1176/ajp.156.10.1522
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and Predictive Validity of the Personality Disorder Diagnosis in Adolescent Inpatients

Abstract: The diagnosis of personality disorder in adolescent inpatients has good concurrent validity; however, the predictive validity of the diagnosis is mixed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 77 publications
(55 reference statements)
2
76
0
13
Order By: Relevance
“…Using the Global Assessment of Functioning (GAF), the Symptom Checklist-90-R (SCL-90R), and a measure of drug use and future hospitalizations, it was concluded that adolescent BPD was partly indicative of future impairments. Although the diagnosis among adolescents was not predictive of a lower score on the GAF or the SCL, those who met criteria for BPD were more likely to engage in drug use and were more likely to have future psychiatric hospitalizations (Levy et al, 1999).…”
Section: Validity Of Adolescent Bpdmentioning
confidence: 76%
“…Using the Global Assessment of Functioning (GAF), the Symptom Checklist-90-R (SCL-90R), and a measure of drug use and future hospitalizations, it was concluded that adolescent BPD was partly indicative of future impairments. Although the diagnosis among adolescents was not predictive of a lower score on the GAF or the SCL, those who met criteria for BPD were more likely to engage in drug use and were more likely to have future psychiatric hospitalizations (Levy et al, 1999).…”
Section: Validity Of Adolescent Bpdmentioning
confidence: 76%
“…Dies führt zu Auffälligkeiten im Wahrnehmen, Denken, Fühlen und in der Beziehungsgestaltung, was wiederum mit subjektivem Leiden des Betroffenen und/oder seiner Umgebung verbunden ist. Als Ausschlusskriterium gilt, dass die Auffälligkeiten durch keine andere psychische oder hirnorga- Wichtig ist ebenfalls, dass bei der Frage nach der Stabilität von Persönlichkeitsmerk-malen das Konzept der "Heterotypen Kontinuität" beachtet wird (Rutter, 1989 In einer zunehmend großen Zahl internationaler Publikationen werden inzwischen Ansätze beschrieben, Persönlichkeitsstörungen im Jugendalter zu diagnostizieren (Bernstein, Cohen, Skodol, Bezirginian, 1996;Levy et al, 1999;Ludolph et al, 1990;Westen u. Chang, 2000;Westen, Shedler, Durrett, Glass, Martens, 2003). Wenn die Diagnose mit Hilfe von strukturierten Interviews gestellt wird, unterscheidet sich die Häufigkeit von Persönlichkeitsstörungen im Alter von 12-17 Jahren kaum von derjenigen bei Erwachsenen im Alter von 18-37 Jahren (Grilo et al, 1998; …”
Section: Was Ist Eine Persönlichkeitsstörung?unclassified
“…In den Studien mit stationären Patienten wurden am häufigsten Borderline-PS (BPS) gefunden (Levy et al, 1999). Brunner et al (2001) wiesen eine Prävalenz von 20 % BPS in einer deutschen klinischen Stichprobe nach.…”
Section: Persönlichkeitsstörungenunclassified
“…Mehrere amerikanische Studien dokumentieren ein ähnlich hohes Vorkommen von PS im Jugendalter wie im Erwachsenenalter (Levy et al, 1999;Westen et al, 2003). Trotz der inzwischen empirisch abgesicherten, validen Diagnostizierbarkeit von PS ab dem Alter von 14 Jahren (Levy et al, 1999;Westen et al, 2003;Übersicht: Krischer et al, 2006Übersicht: Krischer et al, , 2007a überwiegen in der Praxis Bedenken gegenüber einer zu frühen Festlegung -und damit einem "Labeling" -von Kindern und Jugendlichen durch eine solche Diagnose (Schmitz, 1999;Übersicht: Adam u. Peters, 2003). Die Klassifikationsmanuale ICD-10 und DSM-IV sehen davon ab, eine Persönlichkeitsstörungsdiag-nose vor dem 17.…”
Section: Persönlichkeitsstörungenunclassified
See 1 more Smart Citation